Wine : a scientific exploration / Editor: Merton Sandler, Roger Pinder - Pinder, Roger Edited
Wine science is on a roll. It has become the stuff of the popular press, magazines, radio and television. Pundits abound. Some of us are lucky enough to be able to combine our vinous and scientiﬁc interests. A little of what you fancy seems to be a good guiding principle for the health beneﬁts of wine, taken daily, preferably red and perhaps Merlot or Pinot Noir. We have used the same principle in selecting the topics and authors to be included in this book.